Influence of fluoridated salt on urinary fluoride excretion of adults - Schulte, Andreas G.; Gräber, Ralf; Kasperk, Christian; Koch, Martin Jean; Staehle, Hans Jörg (Caries research, 2002)
After the introduction of fluoridated table salt in the staff cafeteria (VZM) of the Heidelberg University Medical and Dental School, the opportunity was taken to determine urinary fluoride excretion of those eating their main daily meals there. Subjects collected 24-hour urine in three fractions (mornings, afternoons, evenings/nights) before fluoridated table salt was introduced in the VZM, and at 6, 12 and 24 months afterwards. The fluoride concentration in the urine was determined. After 24 months, 127 of the original 200 test persons (study group) and 33 of the 60 persons in the control group could be examined. During this period, each participant in the study group took an average of 3.1 of the main meals each week at noon in the VZM. After fluoridated table salt was introduced at the VZM, fluoride excretion increased only in the afternoon urine of the test group; in this respect, the baseline examination disclosed an average of 33.98 ± 21.18 µg/h, while the follow-up examinations revealed averages of between 39.72 ± 22.58 and 42.44 ± 26.16 µg/h. This difference was statistically significant (Kruskal-Wallis test, p < 0.05). It is recommended that in studies of similar questions, fractions of urine should be collected over 24-hour periods.
Gesehen am 09.02.2021